Teknik Penyembunyian Pesan Pada Citra Digital Menggunakan Metode Kombinasi RC4 Dan Steganografi LSB Berbasis VB - sarmi Ningsih; Siti sundari; khairunnisa (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
The rapid development of technology, makes most people follow the existing developments. Technological developments have made it easy for people to access various things, including messages. There are several risks that can hinder the sending of long-distance messages, including we cannot know whether the message sent reaches the person we are going to. It is possible that the messages we send have been read by unauthorized persons. Therefore, security is needed for a system so that messages sent are not easily stolen by others. One way to secure a system requires a combination of cryptographic methods, namely RC4 (Rivest Code 4) and steganography, namely LSB (Least Significant Bit). The system designed is used to secure information from a message by encrypting it using the RC4 algorithm which is then inserted into the image file using the LSB method. The system designed has two main functions, namely the encryption function for encoding messages and steganography on the image. The second function is the decryption function which aims to extract the image so that the hidden message can be understood.